Effect of nitrogen fertilization on production and chemical composition of a native pasture - Correa, D. do Amaral; Scheffer-Basso, S. M.; Fontaneli, R. S. (Agrociencia Uruguay, 2006)
The work had the objective to evaluate the response of a native pasture of Rio Grande do Sul to nitrogen rates (0, 50, 100, 150 e 200 kg ha-1 N), split into four application after cuts taken at 42 days intervals among September 2003 and March 2004. The dry matter (DM) production ranged from 858 kg ha-1 (November) to 1267 kg ha-1 DM (March), which corresponded to 20.42 and 30.16 kg ha-1.d-1 DM, respectively. The total forage yield increased linearly with N rate (y= 13.38x + 2692.7) resulting in 5420 kg ha-1 MS with 200 kg ha-1 N rate. The cutting horizon density, defined by the relationship between the DM produced and the canopy height, ranged from 47.3 (0 kg ha-1 N) to 76.6 kg MS ha-1 cm-1 (200 kg ha-1 N). The chemical composition was not affected by N. The crude protein, acid detergent fiber and neutral detergent fiber concentration were 8%, 44% and 70% respectively.